Characterisation of Bresaola Products Made from Beef, Veal, Wagyu, Mutton and Lamb - Zhang, Renyu (Auckland University of Technology, 2015)
Bresaola is a traditional Italian preserved meat product processed by salting and curing different cuts of lean bovine meat. Bresaola has been favoured by consumers across the globe owing to the characteristic flavour and low fat content (approximately 3-5%). New Zealand is one of the largest producers and exporters of sheep meat and an important contributor of bovine meat. Bresaola products made from New Zealand veal, wagyu, mutton and lamb were compared with the traditional beef products produced from New Zealand grown animals, in terms of physicochemical properties, sensory qualities and digestibility. Cured products made from beef equivalents had higher protein content and lower intramuscular fat content except for wagyu meat, which was similar as those from sheep meat. Mutton and lamb bresaola had lower moisture content (< 40%) than the bresaola made from cattle meat. All of the products were significantly different (p < 0.05) from each other in terms of instrumental texture quality. Wagyu and mutton bresaola showed significantly (p < 0.0001) lower values in hardiness (22.88 ± 0.65 and 29.66 ± 0.66 kg, respectively) than the rest of products. Instrumental colour results of five products were found with significant variations (p < 0.0001) in terms of redness (a*), lightness (L*) and yellowness (b*). Bresaola made from veal and wagyu contained more MUFAs (54.20 ± 0.305 and 58.20 ± 0.58%, respectively) and wagyu had less PUFAs (3.04 ± 0.04%) than other samples. Beef and lamb had a higher concentration of n-3 PUFAs (7.35 ± 0.29% and 5.91 ± 0.16%, respectively) compared to veal, wagyu and mutton (3.58±0.06%, 1.14±0.04% and 3.14±0.04%, respectively). Lamb was rich in n-6 PUFAs (8.72 ± 0.19%). A low value (< 1.5) of the ratio of n-6 to n-3 fatty acids was detected in all five products, suggesting a favourable balance of two groups of fatty acids reflecting the positive effect on health and prevention of chronic disease. Free amino acids (17 amino acids, including 9 essential amino acids) were identified in bresaola products as the result of muscle proteolysis during curing process with the highest content of total free amino acids in mutton bresaola (2215.85 mg/100 g dry matter). Over 50% of free amino acids found were essential amino acids in all five products. In addition, consumers had significantly different ratings of acceptability for the five cured products, in terms of odour, flavour and overall liking (p < 0.05), except for texture. Wagyu bresaola was the most favoured one for all of the sensory attributes tested, and it was associated with juiciness and tenderness from the projective mapping. Mutton and lamb products were related with more of peppered flavour with sheep meat aroma. Protein digestibility of bresaola products was evaluated by using a static in vitro digestion model. Simulated digestion for mouth, stomach and small intestine was completed over a 5 hr period. The highest digestibility was found in mutton bresaola, while the lowest was found in beef bresaola, releasing the amount of free amino acids (8.976 and 5.560 g/100 g protein, respectively) at the end of the simulated digestion procedure. The highest proportion (63.31%) of essential amino acids were found in wagyu meat after digestion. Overall, the results have shown that dry-cured bresaola products made from New Zealand sheep meat have potential as a commercial product. They had similar qualities in the physicochemical, sensory, and digestibility perspectives to the bresaola made with beef. The findings from the present study may be helpful for giving greater value to New Zealand red meat and increasing the export of New Zealand food products.
Keywords: Bresaola; New Zealand meat; Sheep meat; In vitro digestion; Sensory characteristics